Effects of repeated sheeting on rheology and glutenin properties of noodle dough. (November 2019) - Song, Mengkun; Liu, Chong; Hong, Jing; Li, Limin; Zheng, Xueling; Bian, Ke; Guan, Erqi
Abstract: The influence of repeated sheeting process on rheological and glutenin properties of noodle dough with varied water contents was investigated. Both of the rupture stress and elongation were peaked earlier than the apparent viscosity, and the apparent viscosity was more suitable for tracking the evolution in the microstructure of gluten network. The rupture stress and apparent viscosity were reduced with the increase of moisture content, while the rupture elongation shew the opposite trend. The glutenin macropolymer (GMP) content had no obvious change during the initial sheeting stage and was dramatically decreased as the sheeting process was repeated. Compared with the GMP at water content of 30%, the decreasing rate of GMP was lower at water content of 33% and 36%. The large polymeric glutenin (LPP) disaggregated from GMP was increased as the sheeting passes increased from 0 to 40 except for the water content of 30%, which had a maximum at 20 passes. The LPP can be reduced through dithiothreitol (DTT), suggesting that a repolymerization process involving the formation of new disulfide bonds was induced to LPP after disentanglement. The thiol group content of proteins decreased up to 20 passes and then increased at 40 passes. The results demonstrated the disaggregation of GMP during sheeting was due to physical disentanglement involving hydrophobic bond exposure instead of depolymerization involving covalent bond cleavage. Graphical abstract: Image 10327 Highlights: Apparent viscosity was more suitable for indicating the development degree of gluten network. Repeated sheeting decreased the GMP contents and increased the LPP fraction on the whole. LPP fraction was disaggregated from GMP. The disaggregation of GMP during sheeting was due to physical disentanglement involving hydrophobic bond exposure.